Bronchial responsiveness to adenosine 5'-monophosphate (AMP) and methacholine differ in their relationship with airway allergy and baseline FEV(1) - De Meer, Gea; Heederik, Dick; Postma, Dirkje S (American journal of respiratory and critical care medicine, 2002)
Bronchial hyperresponsiveness (BHR) and inflammation are central hallmarks of asthma. Studies in patients with asthma suggest that BHR to adenosine 5'-monophosphate (AMP) is a better marker of bronchial inflammation than BHR to methacholine. The association between markers of airway inflammation and BHR to methacholine and AMP in a population of young adults, with mild symptoms if any, was evaluated. A total of 230 subjects who participated in a follow-up study on occupational allergy were included. Before exposure to occupational allergens, subjects completed a questionnaire on respiratory symptoms and were tested for atopy, blood eosinophilia (> or =275/mm(3)), and BHR to methacholine and AMP (> or =15% fall in FEV(1)). Risk estimates were expressed as prevalence ratios (PR) and 95% confidence intervals (95% CI). Dose-response slopes (DRS) for methacholine and AMP were compared between healthy control subjects, self-reported allergic rhinitis, and allergic asthma. BHR to AMP was associated with allergic rhinitis (PR 2.51, 95% CI: 1.22;5.17), allergic asthma (PR 4.38, 95% CI: 1.98;9.66), with atopy (PR 3.87, 95% CI: 1.76;8.52), and blood eosinophilia (PR 3.57, 95% CI: 1.48;8.77), but not with baseline FEV(1). BHR to methacholine was inversely related to prechallenge FEV(1) (PR 0.97, 95% CI: 0.96;0.99). For both methacholine and AMP the geometric mean DRS increased along the axis asymptomatic-allergic rhinitis-allergic asthma, but for AMP the increase was the strongest. In this population study among young adults, BHR to AMP refers to allergic background of airway lability and BHR to methacholine is related to a diminished airway caliber.